Studi Petrografi Sinter Silika di Mata Air Panas Garara, Gunung Talang, Kabupaten Solok - Ardian Putra; Dwi Puryanti; Afdal Afdal; Akfiny Hasdi Aimon (Jurnal Fisika Unand, 2026)
Mount Talang is an area that has geothermal potential and on its surface is found many surface manifestations in the form of hot springs. One of the hot springs that produces silica sinter is at Garara hot spring. A petrographic test was carried out to determine mineral content of the silica sinter. Petrographic testing shows a volcaniclastic, hypocrystalline texture with a massive structure, angular-subangular grain shape, grain size <0.1-3.5 mm. The silica sinter consists of plagioclase, pyroxene, biotite and opaque minerals in a volcanic glass matrix, where volcanic glass has the largest content. Because the position of the area where the hot springs come out is in a volcanic range, the presence of volcanic glass and the abundance of minerals or similar altered minerals shows that the sample is influenced by minerals usually contained in volcanic systems.